Propofol–Bispectral Index (BIS) Electroencephalography (EEG) Pharmacokinetic-Pharmacodynamic Model in Patients With Post–Cerebral Hemorrhage Hydrocephalus. (July 2021) - Dahaba, Ashraf A.; Lin, Han; Ye, Xue Fei; Zhang, Nu; Wang, Kun; Reibnegger, Gilbert; Lian, Qing Quan
Background . Titrating hypnotic agents for patients who suffer from a cerebral insult is a challenging task. To date there is no real gold standard to precisely quantify electroencephalography (EEG) response in a fashion that could be utilized for patients with post–cerebral hemorrhage hydrocephaly. While we must administer "as per usual" analgesics for noxious stimuli, we have to administer the hypnotic agents more "sparingly" due to lack of objective monitoring. Methods . We compared 15 adult post–cerebral hemorrhage hydrocephalus patients undergoing ventriculo-peritoneal shunt placement with 15 controls matched for gender and approximate age. We set propofol target controlled infusion estimated plasma concentrations (Cp ) to gradually reach 4 µg/mL over 4 minutes. To precisely quantify post–cerebral hemorrhage mental dysfunction, we used electronically retrieved bispectral index (BIS) and propofol Cp data points to create individual inhibitory monophasic mathematical model for each patient that incorporates an independent hysteresis "lag" function. Results . In post–cerebral hemorrhage patients Cp -BIS curve, C50 (propofol concentration associated with inhibitory 50% BIS response) cutoff point was significantly shifted to the left by 39%. Whereas before infusion and at stable propofol 4 µg/mL aneurismal surgical sides ipsilateral (75 ± 13, 25 ± 9) and contralateral (73 ± 15, 27 ± 9) mean ± SD BIS values were significantly lower than ipsilateral (95 ± 3, 46 ± 12) and contralateral (94 ± 3, 46 ± 12) matched controls. Conclusions . Using BIS as surrogate marker of propofol hypnotic effect, BIS monitoring in patients with post–cerebral hemorrhage hydrocephaly showed a pattern of change and trend that was similar albeit 39% significantly lower than subjects without.